The Use of Grammarly (Generative AI) to Enhance Student’s Writing Skill of Analytical Exposition Text for 11th Grade Students at SMA PGRI Cianjur - Sugara, Ria Dewi Hudayani; Mutiara, Dewi; Muhammad, Aris Setiawan; Khodijah, Sita (Candradimuka: Journal of Education, 2025)
This research was conducted to enhance student’s writing skill of analytical exposition text for 11th grade students of SMA PGRI Cianjur through the use of Grammarly (Generative AI). This research used quantitative research and examined using pre-experimental, pretest-posttest design with one group class, namely 11th IPS grade students to be precise. Grammarly (Generative AI) and Analytical Exposition Text as independent variables and student’s writing skill as dependent v ariable. The instruments that used were writing test and questionnaire via Google form with purposive sampling of 11th grade IPS class consist 11 students from 58 students based on the 11th grade population in total. The result of the test indicates an improvement on student’s writing skill based on the average pretest score shows (75) then the average posttest score shows (80) score, and based on paired sample t- test result where .Sig = 0,02 < 0,05 which means the null hypothesis (H0) is rejected and the alternative hypothesis (HI) is accepted. The findings were supported by student’s responses in implementing Grammarly Generative AI towards their writing skill with the percentage result shows 63,48% equals Agree category. So, it can be concluded that there is an impact and significant effect of using Grammarly (Generative AI) towards student's writing skill.